Lions in the night: dual unity of the pantherine image in San beliefs and its possible origins - Rakitianskaia, Olga (Southern African Humanities, 2019)
In this article, I explore the social and sacral significance of the image of big African cats (lion, Panthera leo, and leopard, Panthera pardus) among Khoisan-speaking hunter-gatherers of southern Africa since the beginning of the 19th century. The comparative study is based on ethnographical material from various groups, related to their daily life, beliefs, rituals, and folklore. I argue that the patherine image in all these contexts and among all the studied groups is essentially dualistic or rather represents a dual unity of seemingly opposed concepts. The big cat is equally associated with life and death, malevolence and benevolence, sickness and healing, killing and protecting, provision and deprivation, friendly insiders and dangerous outsiders. I propose that the origins of this symbolism may be found in the daily life relationship between the hunter-gatherers and real lions, which were included by humans in the important social processes of food sharing.